The effect of negative interest rate policy's implementation on banks' profitability - Pohjanrinne, Petra (2024)
Negative interest rate policy (NIRP) denotes the practice adopted by central banks wherein deposit rates, representing the interest rates at which banks hold their reserves in the central bank, are set below zero. Originating as an unconventional monetary policy response to the aftermath of the global financial crisis in 2009, NIRP aimed to incentivize banks to lend out their reserves, thereby stimulating economic activity. However, banks refrained from setting their own deposit rates below zero, apprehensive of potential deposit withdrawals by customers. As loan rates were reduced, banks experienced a diminution in interest income, which is a significant component of their overall profitability. This thesis explores the effects of NIRP and short-term interest rates during the era of negative policy rates on profitability of banks. Leveraging a panel dataset spanning 1467 banks across the eurozone, Denmark, Japan, Sweden, and Switzerland from 2010 to 2022, and employing a static modelling framework, the analysis reveals nuanced effects. Implementation of NIRP is found to decrease return on average equity, while concurrently increasing share of impaired loans among the sampled banks. In addition, short-term interest rates are associated with lowered return on average equity. Interpreting these findings suggests that as intended by central banks, negative policy rates incentivized banks to increase their lending activities. This increase in lending led to higher share of impaired loans, subsequently reducing profit, equity, and assets of the banks. The reduction in equity was particularly pronounced, leading to a significant decline in ROAE. While it has been argued that loan rates decreased more than deposit rates during the era of negative policy rates, it seems that the reduction in loan rates was not significantly greater than that of deposit rates to substantially impact the banks' interest income. Instead, the observed decrease in profitability can be attributed to the consequences of increased lending.